Narrative in territorial identity - Correa Álvarez, Heidy Ester; Doria López, Félix (IE Revista de Investigación Educativa de la REDIECH, 2021)
The historical memory of peoples is little considered in society and in education, especially in the rural context, where the study of general history is more important than the recognition of narratives that explain the aspects that characterize rural communities. As a strategy that seeks to counteract this reality from the ecological thinking, the present research is carried out with the objective of re-signifying the processes of territorial identity construction from the re-linking of ancestral knowledge pertinent to the challenges posed by ecological thinking in the context of an emerging society, starting from the question: how do the interactions generated from the narrative allow the construction of territorial identity and the valuation of ancestral knowledge? The research uses Participatory Action Research (PAR) to generate horizontal dialogue that allows the voices of rural actors to be heard. In conclusion, it is evident that narratives allow the construction of historical stories in which aspects such as artifacts, buildings, gastronomy, handicrafts, crops, trade and work, play an important role in the history of the people.